Incorporating patients in the development of clinical practice guidelines - Germán Loyola; Daniela Morales; Fanny Leyton; Pablo Alonso-Coello; Javier Bracchiglione (Medwave)
Clinical practice guidelines are a set of recommendations developed systematically and based on the best available evidence. Their purpose is to enable healthcare providers and patients to make the best decisions regarding healthcare interventions associated with a particular clinical condition, considering each patient's specific circumstances. One element that has gained importance recently is considering patient preferences when developing healthcare recommendations to increase adherence to therapeutic measures and patient satisfaction. One way to incorporate these preferences is by including patients or their representatives in developing these tools. Patient participation can take place through their inclusion as members of the development panel and/or at different stages of the guideline development process. This can be achieved through various methods like discussion groups, semi-structured interviews, or surveys. However, challenges still need to be addressed to optimally incorporate patients' perspectives, which, among other reasons, are related to socioeconomic barriers, educational gaps, and the persistence of a paternalistic view of healthcare. This article has been developed in the context of a methodological series on clinical epidemiology, biostatistics, and research methodology carried out by the departments of Research Methodology and Evidence-Based Medicine at the School of Medicine of the University of Valparaíso, Chile.